VClosed reduction and intramedullary pinning in the treatment of adult radial neck - Serbest, Sancar; Gurger, Murat; Tosun, Haci Bayram; Karakurt, Lokman (African Field Epidemiology Network-Afenet, 2015)
Closed reduction and intramedullary pinning ( CIMP) in pediatric radial neck fractures was first reported by Metaizeau in 1980 andsatisfactory results have been published several times. The current literature did not encounter any publication related to the implementation of Metaizeau method to adult patients. We applied Metaizeau technique to an adult radial neck fracture and we have achieved satisfactory results. As this case report is single case of this method applied to an adult, we decided to present this case.
Keywords: Radial neck; fractures; closed reduction; intramedullary pinning; treatment